Which pathways trigger the role of complement in ischaemia/reperfusion injury? - Farrar, Conrad A.; Asgari, Elham; Schwaeble, Wilhelm J.; Sacks, Steven (Frontiers in Immunology, 2012)
Investigations into the role of complement in ischaemia/reperfusion injury have identified common effector mechanisms that depend on the production of C5a and C5b-9 through the cleavage of C3. These studies have also defined an important role for C3 synthesised within ischaemic kidney. Less clear however is the mechanism of complement activation that leads to the cleavage of C3 in ischaemic tissues and to what extent the potential trigger mechanisms are organ dependent – an important question which informs the development of therapies that are more selective in ability to limit the injury yet preserve the other functions of complement where possible. Here we consider recent evidence for each of the three major pathways of complement activation [classical, lectin and alternative] as mediators of ischaemia/reperfusion injury, and in particular highlight the role of lectin molecules that increasingly seem to underpin the injury in different organ models and in addition, reveal unusual routes of complement activation that contribute to organ damage.